Reasons for Practicing and Not Practicing Organic Farming as Perceived by Farmers - Jaganathan, D.; Bahal, Ram; Padaria, R.N. (Indian Journal of Extension Education, 2010)
In India, the area under organic farming has been increasing steadily since 2000 after launching National Programme for Organic Production. The study was conducted to find out the reasons for practicing and not practicing organic farming. A total of 240 farmer comprising 120 organic farmers and 120 inorganic farming randomly from four districts in Tamilnadu constituted the sample for the study. The most important reasons for practicing organic farming were concern for human health improvement in health soil and lower production cost. The most important reasons for not practicing organic farming were unorganized market for organically grown produce, low premium for organic produce and lack of knowledge about organic farming.